Propuesta de un sistema de gestión ambiental para la finca bananera DP1 - Sarango Sánchez, Geovanny Alexander (2015)
The aim of this study was to propose a methodology to audit the current state of the Hacienda DP1, located on the site of San Mike, parish Change Balao, province of Guayas, based on the technical, legal, administrative, economic, environmental and community issues for which a research methodology established Exploratoria- Descriptive-correlational , with the aid of a simple statistical, under a no experimental approach; where audits of different areas of the company were established, allowing a clear picture of the reality that is the management of resources and especially the impact that the environment of the production system DP1 hacienda. Variables of each variable Technical audit, legal audit, Management Audit, economic-financial audit, allowed to have resolved the systematized study of each factor were established, although it was unable to verify the records of the company given that access to this information was limited, the results determined that the proposal for an Environmental Management System for the company DEDAPASA SA, tribute to the sustained development of the community and the region is necessary.